Isotopic tracing of mercury sources in estuarine-inner shelf sediments of the East China Sea. (July 2020) - Sun, Xiang; Yin, Runsheng; Hu, Limin; Guo, Zhigang; Hurley, James P.; Lepak, Ryan F.; Li, Xiangdong
Abstract: Large river estuarine-inner shelf systems play an important role in the coastal biogeochemical cycling of heavy metals; however, the source-to-sink of mercury (Hg) in these environments remain poorly understood. In this study, the Hg isotopic composition of surface sediments in the Yangtze River Estuary (YRE) and inner shelf of the East China Sea (ECS) were examined to quantitatively track Hg sources in this region. We detected large spatial variation in δ 202 Hg (−1.88 to −0.29‰) and Δ 199 Hg (−0.22 to 0.13‰) in sediments of the YRE-ECS inner shelf. The impact of sediment resuspension and transport from the YRE to the inner shelf of the ECS could have little effect on Hg isotopic composition, and the two regions shared similar Hg isotopic composition. An isotope-based triple mixing model further revealed major contributors to sediment Hg from industrial Hg discharge into water (51.8 ± 24.5%), soil Hg from surface runoff (29.2 ± 17.0%), and precipitation-derived atmospheric deposition Hg (19.1 ± 17.5%). The Hg isotopic compositions of the YRE sediments and other local river estuaries were similar to those of direct industrial Hg discharge, indicating that contaminated riverine discharge was the dominant Hg source for estuarine and adjacent shelf areas. Soil Hg delivered through surface runoff was the primary source of Hg to the coastal areas not near large river estuaries, whereas precipitation-derived atmospheric deposition had a greater influence on offshore sediment Hg content. Industrial Hg discharged to rivers had the highest mean depositional flux (35.0 ± 27.3 ng cm −2 yr −1 ) and mass inventory (25.6 t yr −1 ), accounting for 77.4% of the total Hg variance. The findings of this study demonstrate that large rivers such as the Yangtze River can supply substantial amounts of industrial Hg to the estuary and adjacent shelf. Graphical abstract: Image 1 Highlights: Hg isotopic compositions in sediments in the YRE–ECS inner shelf were examined. Three major Hg contributors to sediments were revealed by an isotope-based mixing model. Large river industrial Hg discharge was the dominant Hg source in the YRE-ECS inner shelf. Abstract : Quantitatively tracing the sources of mercury in estuarine-inner shelf sediments of the East China Sea based on Hg isotopic composition.